CAROTENOID OF GOLD FISH (Carassius auratus) GIVEN BY PUMPKIN FLOUR, CARROT FLOUR AND SPIRULINA - khairunnisa, khairunnisa; Waspodo, Saptono; Setyono, Bagus Dwi Hari (Jurnal Perikanan Unram, 2020)
Color is one of the most influential factors on the selling price of ornamental fish, but the color of ornamental fish generally fades when kept in an aquarium. The purpose of this study was to determine the carotenoid content of goldfish (Carassius auratus) after being given additional feed in the form of pumpkin flour, carrot flour and spirulina flour. This research was conducted from 30 May to 29 June 2019. This study used a Completely Randomized Design (CRD) method with 4 treatments and 3 replications each of 15 fish per unit, and there were four treatment doses. P0 (without the addition), P1 (with 15% pumpkin flour), P2 (with 5% carrot flour), P3 (with 1.2% spirulina flour). The highest TCF value is in P2 (addition of 5% carrot flour) with a value of 6.4 and the lowest in P0 (without the addition) with a value of 3.7. The highest carotenoid content is in P2 (5% addition of carrot flour) with a value of 11.19 µmol/g while the lowest content is in P0 (without the addition) with a value of 4.65 µmol/g. The treatment did not have a significant effect on the growth and weight of the goldfish.